PENGARUH DISIPLIN KERJA, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PUSKESMAS KRAGAN II KABUPATEN REMBANG - Syakur, Ahmad; Tahwin, Muhammad; Dewi, Dian Ayu Liana; Sodiq, Fajar (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
This research was conducted at the Kragan II Rembang Community Health Center. The aim of this research is to prove and explain the influence of work discipline, organizational culture and work motivation on the performance of employees at the Kragan II Rembang Community Health Center. The population in this study were employees of the Kragan II Rembang Community Health Center. The data collection technique used a questionnaire distributed to 88 respondents. The sampling technique uses saturated samples. The data analysis technique used is multiple linear regression analysis. The results of the research are that work discipline, organizational culture, work motivation partially have a significant positive effect on the performance of employees at the Kragan II Rembang Community Health Center. The adjusted R-square value is 0.634, meaning the contribution of work discipline, organizational culture and work motivation is 63%, while the remaining 37% is explained by other variables not examined in this research.